SISTEM BERPERKARA MELALUI E-COURT DI PENGADILAN NEGERI SUNGGUMINASA PERSPEKTIF SIYASAH DUSTURIYAH - Akmal, Muh. Khairul; Samin, Sabri; Halimang, St. (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
The Supreme Court has answered the demands of the times by making new innovations digitally, namely case administration services with an electronic system (e-court) which is regulatively regulated through Supreme Court Regulation Number 3 of 2018. This study aims to find out how the application of the e-court system in the Sungguminasa District Court and its implications for the application of the justice system is fast, simple, and low cost. This research is a field research with a normative juridical approach. The implementation of the litigation system through e-court has made it easier for justice seekers, especially in the case administration process and the answer-answer stage in the trial. The e-court system, apart from being a form of digital-based service innovation, its existence also contributes to the application of the principle of fast, easy and low-cost justice, because through e-court justice seekers can easily and without being burdened with additional costs such as transportation costs to access the judicial process. The application of the principle of a fast, easy, and low-cost judiciary through the e-court system has a connection with the problem-solving process carried out by the Prophet Muhammad, even at that time, not only quickly and easily but also without any cost.